Clinical diagnosis and mutation analysis of four Chinese families with succinic semialdehyde dehydrogenase deficiency - Ping Wang; Fengying Cai; Lirong Cao; Yizheng Wang; Qianqian Zou; Peng Zhao; Chao Wang; Yuqin Zhang; Chunquan Cai; Jianbo Shu (BMC, 2019)
Abstract Background Succinic semialdehyde dehydrogenase (SSADH) deficiency is a rare autosomal recessively-inherited defect of γ-aminobutyric acid (GABA) metabolism. The absence of SSADH, which is encoded by aldehyde dehydrogenase family 5 member A1 (ALDH5A1) gene, leads to the accumulation of GABA and γ-hydroxybutyric acid (GHB). Few cases with SSADH deficiency were reported in China. Case presentation In this study, four Chinese patients were diagnosed with SSADH deficiency in Tianjin Children's Hospital. We conducted a multidimensional analysis with magnetic resonance imaging (MRI) of the head, semi quantitative detection of urine organic acid using gas chromatography-mass spectrometry, and analysis of ALDH5A1 gene mutations. Two of the patients were admitted to the hospital due to convulsions, and all patients were associated with developmental delay. Cerebral MRI showed symmetrical hyperintense signal of bilateral globus pallidus and basal ganglia in patient 1; hyperintensity of bilateral frontal-parietal lobe, widened ventricle and sulci in patient 2; and widened ventricle and sulci in patient 4. Electroencephalogram (EEG) revealed the background activity of epilepsy in patient 1 and the disappearance of sleep spindle in patient 2. Urine organic acid analysis revealed elevated GHB in all the patients. Mutational analysis, which was performed by sequencing the 10 exons and flanking the intronic regions of ALDH5A1 gene for all the patients, revealed mutations at five sites. Two cases had homozygous mutations with c.1529C > T and c.800 T > G respectively, whereas the remaining two had different compound heterozygous mutations including c.527G > A/c.691G > A and c.1344-2delA/c.1529C > T. Although these four mutations have been described previously, the homozygous mutation of c.800 T > G in ALDH5A1 gene is a novel discovery. Conclusion SSADH deficiency is diagnosed based on the elevated GHB and 4, 5DHHA by urinary organic acid analysis. We describe a novel mutation p.V267G (c.800 T > G) located in the NAD binding domain, which is possibly crucial for this disease's severity. Our study expands the mutation spectrum of ALDH5A1 and highlights the importance of molecular genetic evaluation in patients with SSADH deficiency.